Transformational instructor-leadership and academic performance: a moderated mediation model of student engagement and structural distance. Issue 7 (9th August 2019) - Balwant, Paul T.; Birdi, Kamal; Stephan, Ute; Topakas, Anna
Abstract: Researchers are becoming increasingly interested in the use of transformational leadership theory in higher education teaching (often referred to as transformational instructor-leadership). Much of this body of research investigates a direct association between transformational instructor-leadership and student outcomes. In the present study, we take a step further by investigating (a) student engagement as a mechanism in the relationship between transformational instructor-leadership and students' academic performance and (b) structural distance as a moderator of the relationship between transformational instructor-leadership and student engagement. Using a sample of 183 students across the UK, the findings supported student engagement as a full mediator, but did not support structural distance as a moderator. This study contributes to theory by (a) showing a key underlying process through which transformational instructor-leadership is related to students' academic performance and (b) empirically examining all three dimensions of student engagement. Limitations, suggestions for future research and practical implications are discussed.